Depressive symptom severity mediates the association between avoidant problem-solving style and suicidal ideation - López, Roberto (J Affect Disord, 2020)
BACKGROUND: The contemporaneous association between avoidant style, a maladaptive social problem-solving strategy, and adolescent suicidal ideation has been well established. However, the mechanisms underlying this association are not well understood. Using cross-lagged panel modeling, the present study examined whether depressive symptom severity mediates the relation between avoidant style and severity of suicidal ideation. The specificity of depressive symptom severity as a mediator was also evaluated by simultaneously testing whether avoidant style mediates the association between depressive symptom and suicidal ideation severity. METHODS: The sample included 110 adolescents enrolled in a randomized controlled clinical effectiveness trial. Avoidant style as well as depressive symptom and suicidal ideation severity were assessed via self-report with the Social Problem-Solving Inventory-Revised, Children’s Depression Scale-2, and Suicidal Ideation Questionnaire-Junior, respectively, at baseline, 3- and 6-months. RESULTS: After accounting for participant age, sex, and treatment condition, path analyses supported the specificity of 3-month depressive symptom severity as a mediator of the association between baseline levels of avoidant style and 6-month suicidal ideation severity. LIMITATIONS: Results may not be generalizable to less severe samples. Causality cannot be inferred from study results. Data were exclusively collected via self-report. CONCLUSIONS: Findings suggest that avoidant style is indirectly related to suicidal ideation through depressive symptom severity. Thus, treatment targeted at improving social problem-solving skills, particularly avoidant style, may help reduce depressive symptoms and lower suicide risk.